Community participation in health: A brief review and the experience of Kathmandu Medical College with the Duwakot community - Vaidya, A; Pradhan, B (Kathmandu University Medical Journal, 2009)
One of the principles of Primary Health Care (PHC), Community Participation is a process through which the stakeholders influence and share control over development initiatives and the decisions and resources which affect them. It is a complex issue that has been studied widely and continues to be of great interest among community health workers. This paper presents a brief review of various aspects of community participation. It then illustrates how it is practiced at Duwakot Community Hospital, Kathmandu Medical College, Duwakot, Bhaktapur, Nepal in collaboration with the local community. Key words: Primary Health Care, Community Participation doi: 10.3126/kumj.v6i4.1750 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 526-532